بناء نموذج رياضي لقناة مخبرية تُستخدم للتدريب على التحكم بدرجة الحرارة والتدفق - بلال شيحا; عصام اسعد (Tishreen University, 2018)
Modeling is crucial in all design processes, since the construction of a model which simulates the process implemented on the ground allows for implementations and simulations of tests which may cut substantial costs in case of errors not observed by the designer during the design phase. This paper presents the detailed steps to build two mathematical models in Lab Volt 3522, the first for a duct shaped like Venturi tube used to train students on controlling airflow within it, and can be easily modified to be used with any required gas or liquid. The second is a model of a room of known size and dimensions, located within the designed duct, used to train students on controlling air temperature within it. This paper also shows the steps necessary to design the required PID controller to adjust the airflow value and temperature to match the required value.   تشغل عملية النمذجة أهمية كبيرة في جميع عمليات التصميم، ذلك لأن بناء نموذج تجريبي يحاكي العملية المراد تنفيذها على أرض الواقع يتيح إمكانية تنفيذ اختبارات ومحاكاة قد توفّر كلفةً ماديةً كبيرة في حال وجود أخطاء لم يتم مراعاتها من قِبل المصمم أثناء مرحلة التصميم. يعرض هذا البحث الخطوات التفصيلية لبناء نموذجين رياضيين موجودَين ضمن اللوحة التدريبية Lab Volt 3522، الأول لقناة بشكل أنبوب فينتوري، تُستخدم لتدريب الطلاب على التحكم بتدفق الهواء ضمنها، يمكن تعديلها بسهولة لتُستخدم مع أي غاز أو سائل مطلوب. أما الثاني فهو نموذج لحجرة ذات حجم وأبعاد معروفة ضمن القناة المصمّمة، وتُستخدم لتدريب الطلاب على التحكم بدرجة حرارة الهواء ضمنها. كما يعرض هذا البحث الخطوات اللازمة لتصميم متحكم PID المطلوب لضبط قيمة تدفق الهواء ودرجة الحرارة لتوافق القيمة المطلوبة.